The implementation of the national HIV/AIDS policy in the Vhembe District - Luyirika, Emmanuel B. K. (Emmanuel Bruce Kaweeri) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPA)--University of Stellenbosch, 2003.